Ghost wanted - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2014)
"Bailey Ruth's supervisor, Wiggins, is worried about a dear old friend. The ghost of elegant Lorraine Marlow haunts Adelaide's college library. Known as the Lady of the Roses, she plays matchmaker, using the fragrant flowers to pair up students. But someone's making mischief after hours, leaving roses strewn about the library, destroying a gargoyle, and stealing a valuable book. Concerned with Lorraine's reputation among the living, Wiggins dispatches the irrepressible redhead Bailey Ruth to investigate. Soon after her arrival, trouble begins to stack up. A campus security guard is shot by an intruder, and Bailey Ruth uncovers a catalog of evidence blaming a student for the crimes. As a ghost, she may not be all there, but even Bailey Ruth can decipher that something isn't adding up. So with police preparing to make an arrest, the spirited detective must race against the clock to find the real culprit, because when justice is overdue, it takes more than death to stop Bailey Ruth Raeburn.."--